Desenvolvimento de um gerador síncrono a ímãs permanentes de alta rotação acionado por uma microturbina - Thales Alexandre Carvalho Maia (2016)
A cheap and reliable electrical micro-thermal generator has become a continuing need across power conversion mainly when fuel is available and affordable. The lack of informations regarding micro-turbine systems, mainly due high speeds generator makes the power conversion subject restrict to patented industrial technology. This work presents the electro-mechanical design and test results of a high speed generator directly driven by a micro-turbine. Aiming a high power density, low cost and straightforward design, a commercial automotive turbocharger was used coupled to a permanent magnet synchronous machine. The generator design was performed using finite element method calculation for flux linkage and power density optimization. The stator core presets higher losses at higher frequencies, therefore a need for experimental ferromagnetic characterization was identified. Prototyping procedure was conducted in order to enlighten common vibration sources, which conducted a safely run up to 100,000 rpm under no load. Lab tests where performed with the turbo-machine driven by compressed air and with a three-phase resistive load connected to the generator terminals. The overall system efficiency was estimated based on the fluid energy with a maximum of 3.5 kW of electric power at 70,000 rpm. Simple fabrication procedures can promote an increase in power generation up to 7.2 kW. An overall analysis demonstrates that increasing power and ward off speed limitations is mainly related to concepts regarding higher speeds electrical machines, which are tipically designed using the same principles of lower speeds machines.